2003
DOI: 10.22358/jafs/67781/2003
|View full text |Cite
|
Sign up to set email alerts
|

The effects of selenium and conjugated linoleic acid (CLA) isomers on fatty acid composition, CLA isomer content in tissues, and growth of rats

Abstract: The effects of conjugated linoleic acid (CLA) isomers and/or selenium (as Na 2 SeO 4) on rat growth performance and levels of some fatty acids (FA) in femoral muscles and perigonadal fat were investigated. Feeding a mixture of CLA isomers, the trans-10,cis-12 isomer, or selenium (Se) tended to decrease the rats' body weight compared with the control animals, whereas a diet supplemented with both Se and the trans-10,cis-12 isomer produced the highest increase in body weight gain and the highest feed conversion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
22
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(59 citation statements)
references
References 17 publications
36
22
1
Order By: Relevance
“…Similarly, the diet containing LO and SE effectively increased the body weight of sheep. Thus, our current study is consistent with our previous works (Czauderna et al, 2003b(Czauderna et al, , 2004cKorniluk et al, 2007) showing that diets enriched in selenium (as organic or inorganic seleno-compound) and a precursor of FA containing conjugated double bonds had a similar effect on FCE and BWG of such monogastric animals as laboratory rats (Czauderna et al, 2003b;Korniluk et al, 2007).…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, the diet containing LO and SE effectively increased the body weight of sheep. Thus, our current study is consistent with our previous works (Czauderna et al, 2003b(Czauderna et al, , 2004cKorniluk et al, 2007) showing that diets enriched in selenium (as organic or inorganic seleno-compound) and a precursor of FA containing conjugated double bonds had a similar effect on FCE and BWG of such monogastric animals as laboratory rats (Czauderna et al, 2003b;Korniluk et al, 2007).…”
Section: Discussionsupporting
confidence: 93%
“…So, our current results are in agreement with the observations of Alasnier et al (2002) and our previous studies on rats (Czauderna et al, 2003b(Czauderna et al, , 2004aNiedźwiedzka et al, 2006) showing that in the cells of the pancreas, kidneys, brain, liver, muscles and adipose tissues, t10c12 and t10t12CLA isomers are more efficiently driven through β-oxidation than their 9,11 homologues. In contrast, the amount of c9t11 and t10c12 in the spleen of rats fed the diets enriched in the CLA isomer mixture were similar.…”
Section: The Influence Of Dietary Se-yeast and Cla Isomer(s) On The Asupporting
confidence: 93%
“…The current results are consistent with our earlier studies, which have also indicated that the diet enriched in the t10c12 isomer and inorganic Se (as selenate) is the most potent in terms of elevating the body weight of rats as well as results in the best FCE (Czauderna et al, 2003b(Czauderna et al, , 2004a. Moreover, our results are consistent with other earlier investigations showing that dietary CLA isomer(s) is the most potent factors in terms of antiobesity properties (Alasnier et al, 2002;Belury, 2002;Czauderna et al, 2004b).…”
Section: Impact Of Dietary Se-yeast and Cla Isomers On Rat Growthsupporting
confidence: 93%
See 1 more Smart Citation
“…Se VI , the inorganic selenium compound, reduced BWG (P<0.05) in rats. In accordance with current observations, our previous studies also reported that dietary Se VI was most effi cient in decreasing the feed conversion effi ciency (FCE) in rats (Czauderna et al, 2003c). On the other hand, dosed Se-Y containing mainly seleno-methionine (~85%) (Rayman, 2004) resulted in a negligible infl uence on BWG in rats, which occurred concomitantly with the insignifi cant effect of dietary Se-Y on FCE in rats (Korniluk et al, 2006).…”
Section: Effects Of the Dietary Cla Isomer Mixtures Se VI And Se-y Osupporting
confidence: 88%